A brief review of blockchain-based DNS systems. (27th April 2020) - Al-Mashhadi, Saif; Manickam, Selvakumar
One of the crucial parts of the internet is the domain name system, which works as a phonebook of the internet. The protocol is designed to be fast, reliable, and not shielded with a security mechanism, DNSSEC which adds authentication later. However, threats utilising DNS such as DoS/DDoS are increasing daily. On the other hand, blockchain-based DNS is secure by design. By reviewing and comparing it with the current DNS and its ecosystem, it is concluded that blockchain currently has challenges that need to be addressed before it can be adapted as a replacement for the existing DNS.